Work environment and smoking cessation over a five-year period. - Albertsen K; Hannerz H; Borg V; Burr H (Scandinavian Journal of Public Health, 2004)
AIMS: The authors set out to estimate effects of occupational factors on smoking cessation among Danish employees. METHODS: Data from 3,606 observations of smokers gathered from the Danish National Work Environment Cohort Study in 1990, 1995, and 2000 were analysed by logistic regression. The model comprised background variables, smoking variables, and measures of psychosocial and other aspects of the work environment. RESULTS: Statistically significant odds ratios (OR) for cessation were found for medium versus no exposure to noise (OR 0.71, 95% CI 0.54-0.93), for high versus low physical workload (OR 0.49, 95% CI 0.47-0.73), for high versus low psychological demands (OR 1.42, 95% CI 1.12-1.80), and for medium versus low levels of responsibility at work (OR 1.31, 95% CI 1.03-1.65). CONCLUSION: The probability of smoking cessation differs between people with different exposures to certain work environmental factors.